Implementation of the Experiential Learning Model in the Aqidah Akhlak Subject for Student Character Development at Madrasah Tsanawiyah An-Nur Padang - Galaksi, Galaksi (Program Pascasarjana UMSB, 2025)
The global educational landscape faces persistent challenges in effectively fostering moral character among students, particularly in religious education where traditional didactic methods often fail to bridge the gap between theoretical knowledge and practical ethical behavior. This issue is acute in Islamic education, where subjects like Akidah Akhlak struggle to translate doctrinal teachings into real-world virtues. Experiential learning, with its emphasis on active engagement and reflection, offers a promising solution. This study examines the implementation of experiential learning in Akidah Akhlak classes at MTs An-Nur Padang, Indonesia, aiming to assess its impact on character development and identify actionable strategies for Madrasah reform. Using a qualitative case study design, the research employed in-depth interviews, participant observation, and document analysis to explore how experiential learning structured around Kolb’s cycle enhances moral reasoning and behavior. Data were analyzed through thematic analysis, triangulation, and content analysis to ensure rigor. Results demonstrated significant improvements: 70% of students exhibited heightened engagement through activities like Quranic verse analysis, prophetic storytelling discussions, and collaborative problem-solving. Assessments revealed progress across cognitive (understanding ethics), affective (empathy, discipline), and psychomotor domains. However, challenges included resource limitations, uneven teacher training, and passive participation among 20% of students. The study proposes a four-phase framework for integrating experiential learning in Madrasahs, emphasizing teacher workshops, low-cost media (e.g., digital storytelling), and policy reforms to align with Indonesia’s National Education Goals (UU No. 20/2003). This research contributes to global discourse on moral pedagogy by contextualizing experiential learning in Islamic education, affirming its alignment with Prophetic teaching traditions (tarbiyah nabawiyyah), while highlighting systemic barriers in under-resourced settings.